2016
DOI: 10.1074/jbc.m116.741694
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor-γ Activation Augments the β-Cell Unfolded Protein Response and Rescues Early Glycemic Deterioration and β Cell Death in Non-obese Diabetic Mice

Abstract: Type 1 diabetes is an autoimmune disorder that is characterized by a failure of the unfolded protein response in islet β cells with subsequent endoplasmic reticulum stress and cellular death. Thiazolidinediones are insulin sensitizers that activate the nuclear receptor PPAR-γ and have been shown to partially ameliorate autoimmune type 1 diabetes in humans and non-obese diabetic (NOD) mice. We hypothesized that thiazolidinediones reduce β cell stress and death independently of insulin sensitivity. To test this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Treatment of NOD mice with ML351 led to improved glycemic control and significantly reduced insulitis. The reduction of β-cell death in NOD mice has been suggested to lead to reductions in insulitis, likely by mitigating the chemotactic signals released by dying β-cells ( 4 , 5 ). On the other hand, we observed that galectin 3–positive anti-inflammatory macrophages make up a greater percentage of the insulitic infiltrate, which points to a possible direct effect of the drug on macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of NOD mice with ML351 led to improved glycemic control and significantly reduced insulitis. The reduction of β-cell death in NOD mice has been suggested to lead to reductions in insulitis, likely by mitigating the chemotactic signals released by dying β-cells ( 4 , 5 ). On the other hand, we observed that galectin 3–positive anti-inflammatory macrophages make up a greater percentage of the insulitic infiltrate, which points to a possible direct effect of the drug on macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Maganti et al. reported an increase in β cell mass of pioglitazone-treated non-obese diabetic mice, possibly through induction of ATF4 and BiP and prevention of CHOP upregulation [184] .…”
Section: Therapeutic Modulation Of β Cell Er Stress and Er Stress Sigmentioning
confidence: 99%
“…Results of a Mendelian randomization study refuted a causal role for adiponectin in CV disease (88), which may explain why pure PPARγ agonists, such as rosiglitazone, are not cardioprotective. Finally, PPARγ activation improves pancreatic β cell function and survival by preventing FA-induced impairment of insulin secretion (77) and enhancing the unfolded protein response (89). Thus, whereas PPARα activation leads to energy dissipation, activation of PPARγ stimulates energy storage in WAT, thereby sensitizing liver and peripheral tissues to insulin.…”
Section: R E V I E W S E R I E S : N U C L E a R R E C E P T O R Smentioning
confidence: 99%